The impact of local health professions education grants: is it worth the investment? - Susan Humphrey-Murto (Canadian Medical Education Journal, 2021)
Background: Local grants programs are important since funding for medical education research is limited. Understanding which factors predict successful outcomes is highly relevant to administrators. The purpose of this project was to identify factors that contribute to the publication of local medical education grants in a Canadian context.